ULTRASTRUCTURE OF GASTROINTESTINAL HELMINTHS AND THEIR HISTOPATHOLOGY IN COMMON FISHES OF LEKKI LAGOON LAGOS NIGERIA (2012)
Parasitic infections of fish constitute one of the problems in aquaculture. The pathological conditions resulting from such infections cause significant mortalities among infected fish hosts. There is limited information on fish helminth parasites ultrastructure that could provide guidelines for the identification and confirmation of parasite species that have been associated with economic losses in fishes. Thus, this study was undertaken to describe the fine surface morphology of helminth parasites and pathological conditions associated with helminthes infections. A total of 3040 randomly selected fishes belonging to eight families (Clariidae, Channidae, Mochokidae, Polypteridae, Bagridae, Malapteruridae, Cichlidae and Gobiidae) were procured from landing centres of fishermen from Lekki lagoon between November 2008 and November 2010. Fish samples were dissected and their gastrointestinal parts were examined for parasites and histopathology in physiological saline by microscopy. The parasites recovered were fixed in 70% alcohol and 2.5% glutaldehyde and examined for ultrastructural morphological details with scanning electron microscope. The infected gastrointestinal parts removed were fixed in Bouins fluid and processed using standard histological procedures and examined. Differences in parasite prevalence in relation to host sex were analysed using Chi-square. The parasite species observed were Electrotaenia malopteruri (Proteocephalidae); Indocucullanus genderi and Cucullanus longicollis (Cucullanidae); Procamallanus longus and Spirocamallanus spiralis (Camallanidae); Wenyonia spp. and Caryophyllaeus syrdarjensis (Caryophyllaeidae). Previously unreported ultrastructural features of some helminth parasites observed included wider disc-shaped rostellum-like organ, bean shaped unilocular suckers and lack of median line in between the unilocular suckers in E. malopteruri; lateral extension of cuticle and tail not curved in Procamallanus longus. Other previously unreported ultrastructural features included the presence of papillae at the caudal region, lack of distinct cephalic region and posterior end not bluntly pointed in Wenyonia spp.; single amphid and two submedian cephalic papillae in Cucullanus longicollis and spines on the curved tail in Indocucullanus genderi. Two additional lateral papillae and two small lips were observed in the mouth of Caryophyllaeus sp. The highest mean intensity of infection (7.8?19.5) was recorded for S. clarias with presence of necrotic debris within the gut lumen. Malapterurus electricus with a mean intensity of infection of (0.71?3.39) had necrosis of intestinal surface epithelium. Parachanna obscura with a mean intensity of (0.33?1.01) had hyperplasia of intestinal villi. The lowest mean intensity of infections (0.04?0.19) was recorded in Calamoichthys calabaricus with diffuse necrosis of the intestinal mucosa. Only E. malopteruri was found in M. electricus. In Tilapia zillii, Indocucullanus sp (35.7%) and Cucullanus sp (64.3%) were found while Procamallanus sp (59.4%) and Spirocamallanus sp. (40.6%) were found in P. obscura. In Synodontis clarias, Wenyonia spp (96.5%) and Caryophyllaeus sp. (3.5%) were found. Significant difference in the prevalence of infection between male and female fish host was observed in Synodontis filamentosus (p<0.01). Ultrastructural variations indicated increased precision in identification and confirmation of the parasites in the examined fish hosts. The different pathological lesions could have negatively affected these fishes and this could threaten the abundance and diversity of resident fish species in Lekki lagoon.